2004
DOI: 10.1016/j.jcf.2004.05.048
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin allotypes and IgG subclass antibody response to Aspergillus fumigatus in cystic fibrosis patients

Abstract: An influence of the GM allotypes on the immune response to Af. and on the development of ABPA in patients with CF is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…3 Age data for 20 adult controls shown, age data missing from 20 controls, but all were under 18 years of age. 4 Sex data missing from 10/40 controls. 5 Mutation in the cystic fibrosis transmembrane conductance regulator gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Age data for 20 adult controls shown, age data missing from 20 controls, but all were under 18 years of age. 4 Sex data missing from 10/40 controls. 5 Mutation in the cystic fibrosis transmembrane conductance regulator gene.…”
Section: Discussionmentioning
confidence: 99%
“…A serological test could potentially guide disease management, a principle which is in use for other CF pathogens. [3][4][5][6][7][8] Relying on serology alone to diagnose chronic infection in CF is not sufficient, 9 but combining antibody measurements with culture results can yield simultaneously good sensitivity and specificity. 10 One approach is to comprehensively screen CF populations for antibodies and then reserve frequent sputum culturing for those, who are antibody positive.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that elevated serum concentrations of IgG4 is sometimes observed in severe asthma (14), but it was not observed in mild or typical asthma (15). Anti-aspergillus fumigatus IgG4-antibodies were detected in the patients with allergic bronchopulmonary aspergillosis complicated with cystic fibrosis (16). It will be necessary to comprehensively analyze IgG subclasses in other disorders, but it is traditionally suggested that the IgG4 is concerned with allergy (17,18).…”
Section: F I G U R E 2 T H E R E N a L S P E C I Me N Wi T H A N T mentioning
confidence: 99%
“…Patients with CF are followed closely for their entire lives and there might be a benefit in using serodiagnosis as a complement to routine culture, in the same way that antibodies against Pseudomonas aeruginosa and Aspergillus are used successfully in many CF centres [15][16][17][18][19]. Limitations in the predictive values of such assays have been reported [20], and currently antibody measurements for P. aeruginosa are used clinically in combination with culture results, rather than as stand-alone tests [21].…”
Section: Introductionmentioning
confidence: 99%